Mr. Clyde T. Hardy, Jr. - (:unkn) unknown (Coy C. Carpenter Library)
Info from OH# 24-Clyde Hardy AND 9:197, p. 23
This 1985 photo shows Mr. Clyde Hardy, Jr. giving a speech at the Old Town Club in Winston-Salem at the portrait unveiling of Dr. Eben Alexander, Jr. Mr. Hardy accepted the first hospital administrator position at Bowman Gray School of Medicine as the Director of the Private Diagnostic Clinics. The clinic consisted of individual specialists who came to the new medical school from the community and supported themselves primarily from their own private practice patients. The Private Diagnostic Clinic officially opened on November 15, 1941 but closed in June of 1959 due to fluctuations in different physician salaries. After some reorganization changes, the name was changed from the PDC to the Department of Clinics. Mr. Hardy remained the administrative head of this department.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth